2000
DOI: 10.1385/abab:83:1-3:115
|View full text |Cite
|
Sign up to set email alerts
|

Secretory Immunoglobulin A from Healthy Human Mothers' Milk Catalyzes Nucleic Acid Hydrolysis

Abstract: The human milk secretory immune system is the first line of protection for the newborn infant against various pathogens. Secretory IgA (sIgA), the typical immunoglobulin found in secretions, can fight infections through many mechanisms. Using different methods, we have shown that sIgA from the milk of healthy women possesses DNAse and RNAse activities. The catalytic center is localized in the light chain of catalytic sIgA, while the DNA-binding center is predominantly formed by its heavy chain. The enzymic pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
102
0
3

Year Published

2003
2003
2012
2012

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 72 publications
(111 citation statements)
references
References 25 publications
6
102
0
3
Order By: Relevance
“…Some cytotoxic Abs to microorganisms or mammalian cells trigger target cell death by DNA or protein hydrolysis (53)(54)(55)(56)(57)(58)(59) or by production of toxic oxidative molecules (i.e., H 2 O 2 , O 3 , and hydroxide radials) via catalyzing water oxidation reactions (13)(14)(15). Our data exclude the possibility that the anti-O6ad Abs exert their bactericidal action through DNase (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 73%
“…Some cytotoxic Abs to microorganisms or mammalian cells trigger target cell death by DNA or protein hydrolysis (53)(54)(55)(56)(57)(58)(59) or by production of toxic oxidative molecules (i.e., H 2 O 2 , O 3 , and hydroxide radials) via catalyzing water oxidation reactions (13)(14)(15). Our data exclude the possibility that the anti-O6ad Abs exert their bactericidal action through DNase (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 73%
“…From the crystal structure of a catalytic Ab with an esterase-like activity, p-nitrophenyl ester interacts with amino acid residues in both light and heavy chains of Abzs, and both types of subunits are required for catalysis [25]. The DNAse center of human milk sIgAs is located in the light chain, while the DNA-binding center is mainly formed by the heavy chain [26]. The active site of milk IgGs ATPase is formed by both light and heavy chains of the Abzs at their interface, and the separated subunits are not catalytically active [24].…”
Section: Resultsmentioning
confidence: 99%
“…Natural Abzs also occur in the milk of healthy human mothers and include sIgA and/or IgG possessing DNase and RNase [25][26][27], amylolitic [28] or ATPase activities [29], and protein kinase [30] and lipid kinase activities [31] which are the first examples of natural Abzs with a synthetic activity. Human IgGs from different AD patients in cleavage of supercoiled (sc) and nicked (n) pBR322 DNA: lanes 1-10 correspond to Abs from the sera of 10 different patients; lane C 1 -DNA incubated alone; lanes C 2 and C 3 -DNA incubated with Ab from the sera of two healthy donors.…”
Section: Natural Catalytic Antibodiesmentioning
confidence: 99%
“…We have suggested that DNA-ase and RNA-ase activity Abs from human milk are not only capable of neutralizing viral and bacterial nucleic acids by complexation with them, but also can hydrolyze them; existence of DNA-ase activity in Abs raises the possibility that these Abzs may protect newborns by hydrolysis nucleic acids of infectious agents [26,27].…”
Section: Biological Role Of Abzymesmentioning
confidence: 99%